Content dynamics of heavy metals in bottom sediments and aquatic plants of r. Sozh in the Gomel region - Makaranka, Tatsiana V.; Kasmatskou, Aliaksandr S. (Journal of the Belarusian State University. Ecology, 2018)
The purpose of research was to conduct a comparative analysis of containment and studying of concentration dynamics of heavy metals in bottom sediments and immersed aquatic plants of r. Sozh at different sites for impact determination of city agglomeration of c. Gomel on contamination of r. Sozh. For research there were chosen sites of r. Sozh, located above and below city with the flow of river, that allowed to determine the grade of influence of city agglomeration at pollution of water environment components by heavy metal compounds. The object of research was bottom sediments and immersed aquatic plants of r. Sozh. Content of metals in ashes of plants and bottom sediments was determined by atomic-emission spectral method with spectrophotometer PGS-2. Effluent of c. Gomel influences the accumulation of metals in bottom sediments of r. Sozh, as evidenced by high concentrations of metals in sediments at site of river below the city in comparison with site before taking up the effluent. In most cases with increase of metals concentration in bottom sediments concentration in aquatic plants has been increased too, although close correlation dependencies between this values were not found out. Increase of content of metals in plants in 2016 at all sites of river, albeit insignificantly for some metals, attests transition of metals from bottom sediments to water masses in forms accessible for plants because of changed physic-chemical conditions, associated with abrupt change of water level in r. Sozh. Maximum content of copper and nickel in bottom sediments accounted for different time intervals and different sites of river unlike vanadium and titanium, which maximum concentration was noted in 2014 at site of river below the city.
Keywords: heavy metals; higher aquatic plants; accumulation coefficient; copper; nickel; vanadium; titanium; bottom sediments